Making English a New Latin - Scheuer, Sylwia (Research in Language, 2010)
The paper looks at various aspects of the so-called Latin-English analogy and particularly at the ways in which English may share the fate of Latin in ultimately becoming a victim of its own success. A critical factor in the history of Latin was a conceptual split between its native and non-native varieties, which eventually proved instrumental in establishing its reputation as a dead language. The author wishes to argue that current proposals for a codification of English as a Lingua Franca, aimed at providing vast numbers of L2 learners with a pedagogical alternative that does not emulate L1 standards, may be regarded as major steps towards making English a new Latin: creating a similar split between native versus foreigners' English.